Norms, Power, and the Socially Embedded Realities of Market Taxation in Northern Ghana. (6th March 2017) - Prichard, Wilson; van den Boogaard, Vanessa
Abstract: This article provides a ground-level view of market taxation in two local government areas in Ghana's relatively disadvantaged northern region. It describes a system shaped by informal practices that are grounded in social relationships and collective norms, which sometimes foster greater equity and in other cases serve to reinforce existing inequalities. The evidence suggests the need for a more nuanced understanding of the highly informal and socially embedded realities of local tax collection, and the possibility that improved outcomes could be achieved by "working with the grain" of these inescapable local realities, while seeking to minimize potential costs of informality. Résumé: Cet article donne une vue d'ensemble sur la fiscalité du marché du Ghana dans deux gouvernements locaux relativement désavantagés de la région Nord. Il décrit un système marqué d'une par des pratiques informelles ancrées dans les relations sociales et de l'autre dans des normes collectives, qui parfois favorisent une plus grande équité et dans d'autre cas servent à renforcer les inégalités existantes. La preuve suggère la nécessité d'une compréhension plus nuancée d'une réalité très informelle et socialement intégrée du recouvrement des impôts locaux et la possibilité que des résultats améliorés puissent être obtenus en "travaillant avec le grain" de ces réalités locales incontournables, tout en cherchant à minimiser les coûts potentiels d' informalité.